DXA and pQCT predict pertrochanteric and not femoral neck fracture load in a human side‐impact fracture model. Issue 1 (6th September 2013) - Gebauer, Matthias; Stark, Olaf; Vettorazzi, Eik; Grifka, Joachim; Püschel, Klaus; Amling, Michael; Beckmann, Johannes
Abstract The validity of dual energy X‐ray absorptiometry (DXA) and peripheral quantitative computed tomography (pQCT) measurements as predictors of pertrochanteric and femoral neck fracture loads was compared in an experimental simulation of a fall on the greater trochanter. 65 proximal femora were harvested from patients at autopsy. All specimens were scanned with use of DXA for areal bone mineral density and pQCT for volumetric densities at selected sites of the proximal femur. A three‐point bending test simulating a side‐impact was performed to determine fracture load and resulted in 16 femoral neck and 49 pertrochanteric fractures. Regression analysis revealed that DXA BMD trochanter was the best variable at predicting fracture load of pertrochanteric fractures with an adjusted R2 of 0.824 (p < 0.0001). There was no correlation between densitometric parameters and the fracture load of femoral neck fractures. A significant correlation further was found between body weight, height, femoral head diameter, and neck length on the one side and fracture load on the other side, irrespective of the fracture type. Clinically, the DXA BMD trochanter should be favored and integrated routinely as well as biometric and geometric parameters, particularly in elderly people with known osteoporosis at risk for falls. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:31–38, 2014.